Proyecto de factibilidad para la producción y comercialización de cigarrillos herbales en la ciudad de Loja. - Guamán Pinzón, Jackeline Lizbeth (2024)
The feasibility project for the production and marketing of herbal cigarettes in the city of Loja aims to determine the financial viability of offering a healthy alternative to the consumer through a cigarette made from mint, lavender and chamomile. The work is descriptive with a mixed approach, applying the deductive and inductive method with techniques of bibliographic review and surveys, the segment chosen was the population over 18 years old and a sample of 384 surveys was calculated. The market study identified an unsatisfied demand of 16,995 packs, and the marketing plan detailed aspects of product presentation and how the product will be introduced to the market. In the technical study the production capacity will be 16,900 packs of herbal cigarettes per year, being the same for the 5 years of the project's useful life, the company will be constituted as a Compañía de Responsabilidad Limitada whose corporate name will be GUAPIN Cía. Ltda.; the financial study details the investment that amounts to $73,713.80; being 89% contributed by partners and 11% financed (loan), the sale price to intermediaries is $5.83 per pack, obtaining an annual income of $98,446.75. The values of the financial evaluation are: NPV of $11,574.56; the IRR with 15.18%; the CBR is $1.34, the PRC will be given in 4 years, 8 months and 19 days, the sensitivity analysis supports an increase in costs of 6.40% and decrease in income at 4.79%, which these indicators represent that the profitability of the project is not cancelled. Therefore, it is concluded that the project is acceptable for implementation.